Malaysian Muslim Tourist’s Travel Pattern for Travelling in Hat Yai District, Songkhla Province - หว่าหลำ อับดุลฮันนาน; จินดาบถ ธีรศักดิ์; รัตนพันธุ์ ณัฐกานต์ (KKBS Journal of Business Administration and Accountancy, 2019)
This research aims to investigate the Malaysian Muslim tourist’s travel pattern in Hat Yai district, Songkhla province, and to study the Malaysian Muslim tourist’s preference toward travel pattern in Hat Yai district, Songkhla province. The sample is 400 of Malaysian Muslim tourists in Hat Yai district. The self-administered questionnaire had been collected. Descriptive statistics and Factor Analysis were analyzed with software package. The results show that, three travel patterns of the Malaysian Muslim tourist are identified, which are Natural tourism, Cultural tourism, and Special interest tourism. The preference toward the travel pattern is significant different based on age, education, income, and occupation. Hat Yai district, Songkhla province is suggested to develop the Cultural tourism to satisfy the travel pattern and preference of the Malaysian Muslim tourist.